2010
DOI: 10.1021/jo101680f
|View full text |Cite
|
Sign up to set email alerts
|

Domino Imino-Aldol−Aza-Michael Reaction: One-Pot Diastereo- and Enantioselective Synthesis of Piperidines

Abstract: Addition of α-arylmethylidene- or α-alkylidene-β-keto ester enolate to N-activated aldimines via the imino aldol pathway followed by intramolecular aza-Michael reaction in a domino fashion has been developed, and a highly diastereoselective route to substituted piperidines is reported. Enantiopure piperidines are synthesized from chiral sulfinyl imines. Formation and the observed stereoselectivity of the products have been rationalized by mechanistic and computational studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 113 publications
0
18
0
Order By: Relevance
“…To this homogeneous solution was added 12 36,37 (1.4 g, 5.5 mmol) and NaHCO 3 (0.26 g, 3.0 mmol). The vial was sealed and immersed into a pre-heated oil bath at 90 °C and heated for 16 h. The solution was allowed to cool to room temperature, filtered through a small plug of Celite, and rinsed with CH 2 Cl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…To this homogeneous solution was added 12 36,37 (1.4 g, 5.5 mmol) and NaHCO 3 (0.26 g, 3.0 mmol). The vial was sealed and immersed into a pre-heated oil bath at 90 °C and heated for 16 h. The solution was allowed to cool to room temperature, filtered through a small plug of Celite, and rinsed with CH 2 Cl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Here, we are summarizing some metalfree one-pot approaches for the synthesis of this privileged heterocyclic ring. A highly economical transition metalfree reaction of aryl azides and terminal alkynes (203,204) has been introduced to generate disubstituted 1,2,3-triazoles 205 in excellent yields using aq. NMe 4 OH in DMSO (Scheme 58).…”
Section: Synthesis Of Triazolesmentioning
confidence: 99%
“…Ghorai et al [203] reported a highly enantio-and diasterioselective synthesis of highly substituted piperidines 330 via an imino-Aldol-aza-Michael pathway catalyzed by LDA. The methodology was applied to several α-arylmethylidene-β-keto esters 328 and aryl aldimines 329 to assess the generality of the process.…”
Section: Synthesis Of Piperidinesmentioning
confidence: 99%
“…Piperidine rings are found in the core structure of many naturally occurring alkaloids and drugs [1], such as the potent immunosuppressant rapamysin [2], the amyloglucosidase inhibitor lentiginosine [3] and the anesthetics ropivacaine [4]. L-Pipecolic acid, an important precursor for the production of piperidine derivatives, has an increasing demand worldwide [5].…”
Section: Introductionmentioning
confidence: 99%